Glenodinium triquetrum Ehrenb. is a species not of Heterocapsa F.Stein but of Kryptoperidinium Er.Lindem. (Kryptoperidiniaceae, Peridiniales) - Gottschling, Marc; Tillmann, Urban; Elbrächter, Malte; Kusber, Wolf-Henning; Hoppenrath, Mona (Phytotaxa, 2019)
N/A